Pendampingan Fasilitator dalam Penguatan Kapasitas Masyarakat Menghadapi Bencana Karhutla - Ari Ayuningtyas, Efrinda; Bhaskara, Sufie (Universitas Dinamika, 2026)
Tanah Laut Regency is included in one of the groups of areas that have the potential to experience and be affected by forest and land fires, where the moderate class dominates over the low and high classes. This region has a regulation governing disaster management, namely Regent Regulation No. 79 of 2019 concerning the 2019-2023 Disaster Management Plan. However, the implementation of this regulation has not been optimally felt at the community level due to a lack of socialization and practical application in disaster risk reduction. However, the implementation of non-structural mitigation measures that prioritize community participation has not been fully realized. To support the government's efforts to reduce disaster risk, the BNPB's Disaster Resilient Village program, as outlined in BNPB Regulation No. 1 of 2012, should be implemented. To that end, the objective of this community service activity is to focus on training facilitators who assist communities in identifying potential hazards, vulnerabilities, and capacities, as well as determining disaster risk reduction strategies and building disaster resilience. This activity includes a preparatory stage that covers the selection of facilitator candidates, followed by mentoring activities that include the dissemination of theoretical concepts and practical mentoring practices, and concludes with a learning evaluation. The learning evaluation results show that facilitators are willing to identify and analyze disaster risk assessments covering hazards, vulnerability, and capacity, including reading maps from Google Earth through Focus Group Discussions. The evaluation results indicate the need for follow-up activities to optimize facilitator readiness so that the goal of increasing the capacity of communities to be resilient to forest and land fires can be achieved.